Drought resistance of 2-year-old saplings of Mediterranean forest trees in the field: relations between water relations, hydraulics and productivity (Plant and soil, 2003)
Drought resistance was examined for 2-year-old saplings of Ceratonia siliqua L., Olea oleaster Hoffmgg. et Link., Quercus suber L. and Q. pubescens Willd. growing in the ﬁeld in Sicily, with the aim of testing their possible use in the reforestation of degraded areas. To this purpose, leaf conductance to water vapour (gL), transpiration rate (EL), relative water content (RWC) and water potential (L) were measured between pre-dawn and sunset, monthly from May to November. Parallel measurements of loss of hydraulic conductance of twigs of the current year (PLC) were made together with an estimate of whole-plant hydraulic conductance (KPLANT) on the basis of the ratio of maximum EL to (PD − MIN), where PD is pre-dawn L and MIN is the minimum diurnal L. C. siliqua saplings maintained high gL throughout the study period with high RWC (over 90%) and L. They grew rapidly and increased their foliage area (AL) by over 60% from May to winter rest. This was accompanied by low twig PLC (about 20% in September) resulting in high KPLANT all through the study period. In contrast, O. oleaster saplings underwent distinct dehydration in July, i.e. they showed stomatal closure due to a drop in RWC (to 75%) and L (to the turgor-loss point). This was apparently due to twig cavitation, resulting in a strong decrease of KPLANT. Plants, however, tolerated summer drought, and showed growth (AL increased by 15% from May to November). Saplings of Q. suber and Q. pubescens were much more vulnerable to twig cavitation (PLC was 35–48% from June to November) than the other two species, and their average KPLANT was lower. Saplings of Q. suber and Q. pubescens grew only during the wet spring period, and no new foliage was produced thereafter. Changes in twig hydraulic conductance played a dominant role in determining changes in KPLANT in that the two variables were well correlated to each other (r = 0.68 for P = 0.001). We conclude that C. siliqua is an ideal candidate for reforestation of Sicilian degraded areas as is O. oleaster that, however, requires some additional water supply in the summer, at least during the early years after plantation. In wetter locations of Sicily, to an altitude between 0 and 500 m, Q. suber and Q. pubescens can be used for reforestation with expected higher competitiveness of the latter over the former species.

Competitive strategies for water availability in two Mediterranean Quercus species (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.

Seasonal changes of root hydraulic conductance (K RL) in four forest trees: an ecological interpretation (Plant Ecology, 1998)
This paper deals with the possibility of relating root hydraulic parameters to an ecological index describing the continentality/oceanicity of four forest trees. Root hydraulic conductance (KR) of seedlings of Fagus sylvatica L., Quercus ilex L., Quercus suber L. and Quercus pubescens Willd. was measured in May, August and November 1996. KR was calculated in terms of the relation of the water ﬂow through intact root systems in situ measured with the pressure chamber, and the pressure driving the ﬂow. The sufﬁciency of the root system to supply the foliage was estimated by dividing KR by the seedlings leaf surface area (AL) thus obtaining KRL. In the spring, KRL was largest in F. sylvatica and smallest in Q. pubescens with intermediate values recorded in Q. ilex and Q. suber. All the species studied showed a large decline in KRL just prior to the winter rest except for Q. suber which mantained KRL approximately constant through the period of study. In most cases, KRL changed in accordance with analogous changes in the ﬂow. When the total seedlings’ leaf surface area (AL) was plotted versus KRL, it appeared that KRL of Q. pubescens increased with AL, proportionally, while KRL of F. sylvatica was inversely related to AL. This, together with the largest KRL recorded in the summer in Q. pubescens, was interpreted as advantageous to this species (which is adapted to semi-arid environments) in that: (a) roots could supply water to foliage efﬁciently even during the adverse season and (b) the foliage growth could be sustained even in summer. No statistically signiﬁcant relation of KRL to the continentality index calculated for the four species studied on the basis of their European distribution, was found to exist. Nonetheless, our data appear to be encouraging for future research aimed at better interpreting the typical distribution areas of plant species.

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.

Sclerophylly and Plant Water Relations in Three Mediterranean Quercus Species (Annals of Botany, 1990)
The possible role in drought resistance played by sclerophylly was studied in the Mediterranean oaks Quercus ilex, Q. suber and Q. pubescens. Studies were conducted on leaves at 30, 50 and 80% of their final surface area, as well as on mature leaves of the current year's growth in June and September and on 1-year-old leaves.Leaves of different ages of the three species showed quite different degrees of sclerophylly (DS). Q. ilex leaves reached the definitive DS of 1.75 g dm−2 during leaf expansion; Q. pubescens leaves hardened at the end of their expansion, with a final DS of 0.93 g dm−2; Q. suber showed the lowest DS of 0.76 g dm−2.Leaf conductance to water vapour (g1) of 1-year-old leaves of Q. ilex, measured in the field, showed a duration of the g1 peak values about twice that of the other two species. The minimum leaf relative water content (RWC), however, was near the same in the three species, indicating that water loss was recovered partly by Q. ilex leaves. This was apparently due to the higher bulk modulus of elasticity (max) as resulting from leaf water potential isotherms.High correlation coefficients were noted between DS and max but large changes in DS were needed to display minor changes in max. When both DS and max were correlated to the minimum RWC, an increase in DS of 133 % (corresponding to an increase in max of only 12 %) was needed to cause an increase in RWC of 2%. Therefore, sclerophylly cannot be considered as significantly related to a drought-avoiding strategy.

Wood anatomy of some trees with diffuse- and ring-porous wood: Some functional and ecological interpretations (Giornale botanico italiano, 1990)
Abstract The xylem conduit dimensions (i.e. their width and length) have been measured in 1-year-old internodes, nodes and node-to-petiole (N-P) junctions of three species with diffuse-porous wood, namely Ceratonia siliqua L., Laurus nobilis L. and Olea europaea L. as well as of three species with ring-porous wood, namely Quercus ilex L., Q. suber L. and Q. pubescens Willd? The xylem conduit diameter and length distributions have been related to the drought resistance strategies adopted by the six species. C. siliqua and Q. ilex (drought avoiding water spenders) showed the widest xylem conduits (each species within its characteristic pattern of wood anatomy). This is consistent with their high demand of efficient water transport to leaves. L. nobilis (drought avoiding water saver) showed relatively narrow xylem conduits, efficient enough, however, to assure water supply to leaves at the reduced transpiration rate exhibited by the species. O. europaea, Q. suber and Q. pubescens (drought tolerants) showed the narrowest xylem conduits but also the longest ones. The xylem system of C. siliqua and Q. ilex represented a good compromise between efficiency and safety of the water transport, the former as due to wide xylem conduits, the latter to the reduced xylem conduit length as well as to the strong «hydraulic constrictions» at their nodes and N-P junctions. The ecological interpretation of such hydraulic architecture is discussed.
doi: 10.1080/11263509009430260